No war, no peace : the rejuvenation of stalled peace processes and peace accords - Mac Ginty, Roger 1970 (New York : Palgrave Macmillan, 2006)
Many of the peace processes and peace accords over the past decade have ushered in poor quality of peace that makes little difference to the security and standard of living of citizens in post-peace accord societies. This book investigates stalled and dysfunctional peace processes and peace accords in societies experiencing civil wars. Using a critical and comparative perspective, it offers strategies for rejuvenating and re-orientating stalled peace processes and peace accords so that they are more able to foster sustainable and inclusive peace.
Includes index.
Bibliography: p. 215-228.
Keywords: Peace; Peace treaties; Peace-building.